2018
DOI: 10.19080/gjorm.2018.06.555683
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors: The Dirty Dozen in CTG misinterpretation

Abstract: The contribution of human factors to errors and adverse outcomes within most healthcare systems cannot be underestimated. In Obstetrics we rely on the cardiotocograph as a non-invasive tool for detecting fetal hypoxia. However, since its introduction in 1960 the CTG has failed to reduce the rate of hypoxia-induced perinatal morbidity and mortality. The recent Each Baby Counts report indicates that 62% of stillbirths, neonatal deaths, and brain injuries of term babies in labour in 2015 were related to errors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Nzelu [26] showed that communication constraints, distractions, resources constraints, task routine and complacency are among the reasons for the increase in total recordable incident frequency and lost time incident frequency rates in Oil and Gas construction industry. Okeke et al [27] affirmed that rotational work which is a major characteristic of Nigerian Oil and Gas construction industry can be one of the major reasons that contributes to strain in families, marital, career and personal relations which are precursors for incident causation in Nigerian Oil and Gas construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nzelu [26] showed that communication constraints, distractions, resources constraints, task routine and complacency are among the reasons for the increase in total recordable incident frequency and lost time incident frequency rates in Oil and Gas construction industry. Okeke et al [27] affirmed that rotational work which is a major characteristic of Nigerian Oil and Gas construction industry can be one of the major reasons that contributes to strain in families, marital, career and personal relations which are precursors for incident causation in Nigerian Oil and Gas construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human factors draw on principles of physiology and psychology to design products, processes and systems that optimise human productivity, reduce error and ensure safe outcome. 3 7 11 A tool used to illustrate this concept in aviation is the Software, Hardware, Environment, Liveware (SHELL) model. 10 The model stresses the importance of having a good match between ‘liveware’ (people), software, hardware and the environment.…”
Section: Human Factors and The Shell Modelmentioning
confidence: 99%
“…2 Today, the technical aspects of surgery are thought to rarely be the cause of major errors; instead, it is the non-technical factors that are receiving widespread attention. 5–7…”
Section: Introductionmentioning
confidence: 99%